Bio-based epoxy emulsifier, sizing agent, carbon fiber, composite material and preparation methods of bio-based epoxy emulsifier, sizing agent, carbon fiber and composite material
By using bio-based epoxy emulsifiers prepared by polysaccharides and phenolic acids, the problems of toxic raw materials and insufficient monofunctionality in existing sizing agents are solved, and green and environmentally friendly production and the preparation of versatile sizing agents are achieved, and the mechanical properties and production efficiency of composite materials are improved.
Patent Information
- Application Number
- CN202510092751.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing aqueous epoxy emulsifiers have problems with the use of toxic and harmful raw materials and insufficient monofunctionality when preparing sizing agents, resulting in increased environmental pollution and production costs.
A bio-based epoxy emulsifier is prepared by using polysaccharides and phenolic acids as raw materials. The emulsifier is prepared by heating reaction, avoiding the use of organic solvents, and sizing agents can be prepared by reverse method or self-emulsification method to achieve versatility.
It has achieved the avoidance of the use of toxic raw materials in industrial production, reduced the risk of equipment damage, simplified operation, saved time, and the prepared sizing agent is easy to degrade, comply with the sustainable development requirements of modern industry, and has the prospect of large-scale production.
Smart Images

Figure CN119505253A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of sizing agents, and in particular to a bio-based epoxy emulsifier, a sizing agent, a carbon fiber, a composite material and a preparation method thereof. Background Art
[0002] Carbon fiber / epoxy resin composites are widely used in aerospace, medical equipment, automobile transportation, wind power generation and other fields due to their many advantages such as high temperature resistance, friction resistance, corrosion resistance, high modulus and high strength. In the process of industrial production of carbon fiber, due to industrial and process problems, irreversible damage to the fiber itself is inevitable, and a large number of longitudinal grooves and hairs are generated on the fiber surface, which affects the strength of the fiber itself, thereby reducing the mechanical properties of carbon fiber / epoxy resin composites.
[0003] In order to improve the surface condition of carbon fiber, enhance its polarity and interfacial bonding performance with resin, a variety of methods have been proposed, including gas phase oxidation, plasma treatment and gas phase deposition. However, these methods have the risk of directly or indirectly damaging the carbon fiber. In contrast, the sizing method has become an ideal choice for optimizing the surface properties of carbon fiber because of its cost-effectiveness, strong controllability and no damage to the fiber. The sizing method can not only improve the wetting properties of the fiber surface, but also connect the fiber and the matrix through the "chain" effect, provide physical and chemical bonding properties at the interface, and thus improve the mechanical properties of the composite material.
[0004] Although the sizing method has many advantages, the existing water-based epoxy emulsifier still faces some problems when preparing the sizing agent. In particular, the existing emulsifier uses toxic and harmful raw materials during industrial production, which poses a threat to the ecological environment and human health. In addition, the existing emulsifier can usually only achieve a single-function de-emulsified resin, and has no additional contribution to the preparation of subsequent composite materials, resulting in a waste of raw materials and an increase in production costs. This is contrary to the principle of contemporary enterprises to pursue product efficiency and achieve raw material diversification. Taking the Chinese patent with publication number CN100500984C as an example, the patent discloses an emulsion-type sizing agent prepared by mixing a polyimide resin and an epoxy resin. Although this method improves the surface properties of carbon fiber to a certain extent, the prepared sizing agent contains a difficult-to-volatile organic solvent, which is not easy to remove and difficult to degrade, causing serious pollution to the environment. This defect limits its wide application in modern industrial production.
[0005] The present invention aims to solve the above-mentioned problems. Summary of the invention
[0006] In order to solve the above problems, the present invention proposes a bio-based epoxy emulsifier, a sizing agent, a carbon fiber, a composite material and a preparation method thereof. The bio-based epoxy emulsifier can avoid the use of toxic and harmful raw materials in industrial production, realize a variety of methods to prepare a sizing agent, and simultaneously have multiple functions such as protecting fibers, enhancing interface bonding performance and promoting the improvement of mechanical properties of composite materials. The bio-based epoxy emulsifier and the sizing agent prepared using the bio-based epoxy emulsifier are easy to degrade and meet the requirements of sustainable development of modern industry.
[0007] The present invention provides a bio-based epoxy emulsifier, the raw materials of which include the following components: polysaccharide, epoxy resin, phenolic acid and catalyst; The preparation method of the bio-based epoxy emulsifier comprises the following steps: S101: heating the epoxy resin to 50-100° C. until it is completely melted, adding polysaccharide, and reacting at 80-110° C. for 4-15 hours to obtain a polysaccharide-modified epoxy resin; S102: Heat the polysaccharide-modified epoxy resin to 120-200° C., then add phenolic acid and a catalyst, and react for 5-18 hours to obtain a bio-based epoxy emulsifier.
[0008] In one or more embodiments, the mass ratio of polysaccharide to epoxy resin in step S101 is 1:(3-4.5).
[0009] In one or more embodiments, in step S102, the mass ratio of the polysaccharide-modified epoxy resin to the phenolic acid is 1:(0.1-1), and the mass of the catalyst accounts for 0.001%-0.008% of the total mass of the raw materials.
[0010] In one or more embodiments, the bio-based epoxy emulsifier has one or more of the following characteristics: The polysaccharide is selected from one or more of chitosan, chitosan derivatives and chitobiose hydrochloride, and the chitosan derivative is selected from one or more of carboxymethyl chitosan and chitosan oligosaccharide; The epoxy resin is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, diphenol propane type epoxy resin and polyphenol type glycidyl ether epoxy resin; The phenolic acid is selected from one or more of cinnamic acid and cinnamic acid derivatives, and the cinnamic acid derivative is selected from one or more of hydroxycinnamic acid, butyl cinnamate and 4-methylcinnamic acid; The catalyst includes tetrabutylammonium bromide.
[0011] The present invention also provides a sizing agent, comprising a bisphenol A epoxy resin in a mass ratio of 1: (0.25-0.37): (3.34-4): (0.007-0.13): (0.007-0.13), the bio-based epoxy emulsifier as described above, water, a lubricant and an antistatic agent.
[0012] In one or more embodiments, the sizing agent has the structural formula: .
[0013] In one or more embodiments, the sizing agent is prepared by: S111: heating the bisphenol A epoxy resin to a molten state, adding the bio-based epoxy emulsifier to the mixture, and stirring and mixing the bisphenol A epoxy resin and the bio-based epoxy emulsifier with a high-speed shearing machine; S112: After the mixture is stirred and mixed evenly, the rotation speed is increased and water is slowly added to continue stirring and mixing; S113: After stirring and mixing evenly, a lubricant and an antistatic agent are added to obtain a sizing agent.
[0014] The present invention also proposes a sizing agent, comprising the bio-based epoxy emulsifier, amines, water, a lubricant and an antistatic agent as described above in a mass ratio of 1: (0.01-0.15): (2.6-3): (0.007-0.13): (0.007-0.13).
[0015] In one or more embodiments, the sizing agent is prepared by: S121: Cool the bio-based epoxy emulsifier to 50-70°C, then add the amine and stir to mix; S122: Increase the stirring speed to 1000-2000 rpm, slowly add water, and continue stirring and mixing; S123: After stirring and mixing evenly, a lubricant and an antistatic agent are added to obtain a sizing agent.
[0016] The present invention also provides a sizing-treated carbon fiber, which is prepared by sizing the carbon fiber using the sizing agent as described above.
[0017] The present invention also provides a carbon fiber / epoxy resin composite material, which is prepared by curing the sizing-treated carbon fiber, epoxy resin and curing agent in a mass ratio of 1:(100-200):(10-20) as described above.
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. The bio-based epoxy emulsifier provided by the present invention uses polysaccharides and phenolic acids as raw materials, and has the advantages of easy raw material availability, high yield, simple operation and high degradation efficiency. When preparing a sizing agent, the emulsifier does not require the use of an organic solvent, thereby avoiding equipment damage, achieving green and environmentally friendly production, and having the prospect of large-scale production and application.
[0019] 2. The bio-based epoxy emulsifier provided by the present invention has multiple functions and can be used as a surfactant to emulsify epoxy resin by a phase inversion method. At the same time, a simpler self-emulsification method can be used to directly prepare a water-based sizing agent without the need to prepare an emulsifier in advance, thereby simplifying the operation and saving time.
[0020] 3. The sizing treated carbon fiber provided by the present invention contains double bonds, which are prone to undergo cycloaddition reaction under ultraviolet irradiation, thereby shortening the curing time of the composite material. The preparation of composite materials with ultraviolet curing resin not only has low energy consumption, low pollution, low cost, but also has excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is an infrared chromatogram characterization diagram of the sizing agent prepared in Example 1 of the present invention.
[0022] Figure 2 This is the thermogravimetric diagram of the sizing agent prepared in Example 2 of the present invention.
[0023] Figure 3 This is a surface morphology image (SEM) of the sizing-treated carbon fiber prepared in Example 3 of the present invention.
[0024] Figure 4 This is a surface morphology image (SEM) of the sizing-treated carbon fiber prepared in Example 4 of the present invention.
[0025] Figure 5 This is a surface morphology (SEM) of the carbon fiber recovered after degradation of the carbon fiber / epoxy resin composite material prepared in Example 4 of the present invention.
[0026] Figure 6 It is a schematic diagram of the comparison of the interlaminar shear strength of the carbon fiber / epoxy resin composite materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the invention and are not used to limit the invention.
[0028] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0029] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0030] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0031] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0032] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0033] The invention provides a bio-based epoxy emulsifier, the raw materials of which include the following components: polysaccharide, epoxy resin, phenolic acid and a catalyst.
[0034] In the present invention, the polysaccharide is selected from one or more of chitosan, chitosan derivatives and chitobiose hydrochloride. Among them, the chitosan derivative can be one or more selected from carboxymethyl chitosan and chitosan oligosaccharide.
[0035] In the present invention, the epoxy resin is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, diphenol propane type epoxy resin and polyphenol type glycidyl ether epoxy resin.
[0036] In the present invention, the phenolic acid is selected from one or more of cinnamic acid and cinnamic acid derivatives. Among them, the cinnamic acid derivatives can be one or more selected from hydroxycinnamic acid, butyl cinnamate and 4-methylcinnamic acid.
[0037] In the present invention, the catalyst includes but is not limited to tetrabutylammonium bromide catalyst.
[0038] The preparation method of the bio-based epoxy emulsifier comprises the following steps: S101: heating the epoxy resin to 50-100° C. until it is completely melted, adding polysaccharide, and reacting at 80-110° C. for 4-15 hours to obtain a polysaccharide-modified epoxy resin; S102: heating all the polysaccharide-modified epoxy resins obtained in step S101 to 120-200° C., then adding phenolic acid and a catalyst, and reacting for 5-18 hours to obtain a bio-based epoxy emulsifier.
[0039] In step S101, the mass ratio of polysaccharide to epoxy resin is 1:(3-4.5). In some embodiments, the mass ratio of polysaccharide to epoxy resin can be 1:(3.5-4.5), or 1:(3-4), or 1:(4-4.5). Preferably, the mass ratio of polysaccharide to epoxy resin is 1:4, or 1:3.33, or 1:4.33.
[0040] For example, the polysaccharide-modified epoxy resin is formed by the reaction of chitosan and bisphenol A epoxy resin in a mass ratio of 1:4, or by the reaction of carboxymethyl chitosan and bisphenol F epoxy resin in a mass ratio of 1:3.33, or by the reaction of chitosan oligosaccharides and diphenol propane epoxy resin in a mass ratio of 1:3.33, or by the reaction of chitobiose hydrochloride and polyphenol glycidyl ether epoxy resin in a mass ratio of 1:4.33.
[0041] In step S102, the mass ratio of the polysaccharide-modified epoxy resin to the phenolic acid is 1:(0.1-1), and the mass of the catalyst accounts for 0.001%-0.008% of the total mass of the raw materials (i.e. the total mass of the polysaccharide-modified epoxy resin, phenolic acid and catalyst added).
[0042] The bio-based epoxy emulsifier provided by the present invention is prepared based on polysaccharides and phenolic acids, and the raw materials are easy to obtain, the yield is high, the operability is strong, and the degradation efficiency is high. Moreover, in the process of preparing the sizing agent using the bio-based epoxy emulsifier prepared by the present invention, no organic solvent is used, which avoids damage to the equipment and is green and environmentally friendly, and has an application prospect of large-scale production. In addition, the bio-based epoxy emulsifier provided by the present invention is multifunctional, and the bio-based epoxy emulsifier can be used as a surfactant to emulsify the epoxy resin through the phase inversion method, and the water-based sizing agent can also be directly prepared by the self-emulsification method, which is simple to operate and saves time.
[0043] The present invention also provides a sizing agent, comprising a bisphenol A epoxy resin in a mass ratio of 1: (0.25-0.37): (3.34-4): (0.007-0.13): (0.007-0.13), the bio-based epoxy emulsifier as described above, water, a lubricant and an antistatic agent.
[0044] In the present invention, the lubricant is selected from one or more of polyoxyethylene ether, butyl stearate, higher fatty amine and higher fatty alcohol. In the description of lubricant selection herein, "higher fatty amine" and "higher fatty alcohol" refer to those fatty amines and fatty alcohols with relatively long carbon chains. For example, higher fatty amines refer to amine compounds with longer carbon chains, usually fatty acids containing 12 or more carbon atoms. Higher fatty alcohols refer to alcohol compounds with longer carbon chains, usually also containing 12 or more carbon atoms.
[0045] In the present invention, the antistatic agent is selected from one or more of polyetheresteramide, polyetheresteracetamide, polyethylene oxide and propylene oxide copolymer.
[0046] Preferably, deionized water is used.
[0047] In some embodiments, the sizing agent comprises a bisphenol A epoxy resin, a bio-based epoxy emulsifier as described above, water, a lubricant, and an antistatic agent in a mass ratio of 1: (0.26-0.3): (3.44-3.7): (0.01-0.11): (0.04-0.08).
[0048] In some embodiments, the sizing agent comprises a bisphenol A epoxy resin, a bio-based epoxy emulsifier as described above, water, a lubricant, and an antistatic agent in a mass ratio of 1:0.28:(3.54-3.6):(0.05-0.09):0.06.
[0049] Preferably, the sizing agent comprises bisphenol A epoxy resin, the bio-based epoxy emulsifier as described above, water, a lubricant and an antistatic agent in a mass ratio of 1:0.28:3.6:0.05:0.06, or comprises bisphenol A epoxy resin, the bio-based epoxy emulsifier as described above, water, a lubricant and an antistatic agent in a mass ratio of 1:0.28:3.54:0.09:0.06.
[0050] The preparation method of the sizing agent is a phase inversion method, in which the bio-based epoxy emulsifier is used to emulsify bisphenol A epoxy resin. The preparation method of the sizing agent comprises the following steps: S111: heating the bisphenol A epoxy resin to a molten state, adding the bio-based epoxy emulsifier to the mixture, and stirring and mixing the bisphenol A epoxy resin and the bio-based epoxy emulsifier with a high-speed shearing machine; S112: After the mixture is stirred and mixed evenly, the rotation speed is increased and water is slowly added to continue stirring and mixing; S113: After stirring and mixing evenly, a lubricant and an antistatic agent are added to obtain a sizing agent.
[0051] The present invention also provides a sizing agent, comprising the bio-based epoxy emulsifier as described above, amines, water, a lubricant and an antistatic agent in a mass ratio of 1: (0.01-0.15): (2.6-3): (0.007-0.13): (0.007-0.13).
[0052] The same as the sizing agent described above, in the present invention, the lubricant is selected from one or more of polyoxyethylene ether, top stearic acid, high-grade fatty amine and high-grade fatty alcohol. The antistatic agent is selected from one or more of polyether ester amide, polyether ester acetamide, polyethylene oxide and propylene oxide copolymer. Preferably, water is deionized water. In addition, in the present invention, amines include but are not limited to triethylamine.
[0053] In some embodiments, the sizing agent comprises the bio-based epoxy emulsifier as described above, amines, water, a lubricant, and an antistatic agent in a mass ratio of 1: (0.07-0.15): (2.8-3): (0.02-0.13): (0.08-0.13).
[0054] In some embodiments, the sizing agent comprises the bio-based epoxy emulsifier as described above, amines, water, a lubricant, and an antistatic agent in a mass ratio of 1: (0.09-0.13): 3: (0.08-0.13): (0.1-0.12).
[0055] Preferably, the sizing agent comprises the bio-based epoxy emulsifier, amines, water, lubricant and antistatic agent as described above in a mass ratio of 1:0.13:3:0.13:0.12, or comprises the bio-based epoxy emulsifier, amines, water, lubricant and antistatic agent as described above in a mass ratio of 1:0.09:3:0.08:0.1.
[0056] The preparation method of the sizing agent is a self-emulsification method, comprising the following steps: S121: Cool the bio-based epoxy emulsifier to 50-70°C, then add the amine and stir to mix; S122: Increase the stirring speed to 1000-2000 rpm, slowly add water, and continue stirring and mixing; S123: After stirring and mixing evenly, a lubricant and an antistatic agent are added to obtain a water-based epoxy carbon fiber sizing agent.
[0057] The present invention also provides a sizing-treated carbon fiber, which is prepared by sizing the carbon fiber using the sizing agent described above. Specifically, it comprises the following steps: The commercial carbon fiber (filament) is placed in a container filled with acetone and subjected to a desizing treatment at 50-100°C for 5-24 hours to obtain a desizing carbon fiber; Then, the carbon fiber is placed in a beaker containing the sizing agent described above and soaked for 5 to 15 minutes. The carbon fiber coated with the sizing agent is placed in an oven at 100 to 200° C. for 2 to 30 minutes to obtain sizing-treated carbon fiber.
[0058] When commercial carbon fiber cloth is used as the carbon fiber, the carbon fiber is sizing treated by using the sizing agent described above, including the following steps: The commercial carbon fiber cloth was cut into small pieces of 80×80 mm in size and placed in a container filled with acetone, heated and soaked at 60-120°C for 10-24 hours, washed with deionized water for multiple times, and then vacuum dried at 105-120°C for 4-10 hours to obtain the desizing carbon fiber cloth; Then, the desized carbon fiber cloth is placed in a beaker containing the sizing agent described above and soaked for 30 to 60 minutes. The carbon fiber cloth coated with the sizing agent is placed in an oven at 105 to 120° C. and vacuum dried for 2 to 4 hours to obtain a sizing-treated carbon fiber cloth.
[0059] The present invention also provides a carbon fiber / epoxy resin composite material, which is prepared by curing the sizing-treated carbon fiber, epoxy resin and curing agent described above. In some embodiments, the carbon fiber / epoxy resin composite material is prepared by curing carbon fiber, epoxy resin and curing agent in a mass ratio of 1: (100-200): (10-20). The epoxy resin and curing agent are both excessive to ensure that the carbon fiber is fully impregnated.
[0060] In one embodiment, a method for preparing a carbon fiber / epoxy resin composite material comprises the following steps: Six layers of the sizing-treated carbon fiber cloth described above were laid out and placed in a mold, epoxy resin and curing agent were mixed and bubbles were removed, and then vacuum injected into the mold, cured at 105°C for 2h and 125°C for 2h to obtain a carbon fiber composite material. Among them, different carbon fiber layers have different mechanical properties, and the carbon fiber cloth is relatively uniform by default.
[0061] Preferably, the mass ratio of the epoxy resin to the curing agent is 100: 10. In addition, the curing agent includes but is not limited to diethylenetriamine.
[0062] In some embodiments, the curing is performed under ultraviolet light with a light intensity of 25.0 J / cm -2 Under ultraviolet irradiation, the sizing agent undergoes a cycloaddition reaction with the matrix, which can improve the strength of the composite material. In addition, the preparation of composite materials with ultraviolet curing resin has the advantages of low energy consumption, low pollution, low cost and good performance.
[0063] Compared with the prior art, the present invention has the following beneficial effects: 1. The bio-based epoxy emulsifier provided by the present invention uses polysaccharides and phenolic acids as raw materials, and has the advantages of easy raw material availability, high yield, simple operation and high degradation efficiency. When preparing a sizing agent, the emulsifier does not require the use of an organic solvent, thereby avoiding equipment damage, achieving green and environmentally friendly production, and having the prospect of large-scale production and application.
[0064] 2. The bio-based epoxy emulsifier provided by the present invention has multiple functions and can be used as a surfactant to emulsify epoxy resin by a phase inversion method. At the same time, a simpler self-emulsification method can be used to directly prepare a water-based sizing agent without the need to prepare an emulsifier in advance, thereby simplifying the operation and saving time.
[0065] 3. The sizing treated carbon fiber provided by the present invention contains double bonds, which are prone to undergo cycloaddition reaction under ultraviolet irradiation, thereby shortening the curing time of the composite material. The preparation of composite materials with ultraviolet curing resin not only has low energy consumption, low pollution, low cost, but also has excellent mechanical properties.
[0066] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.
[0067] Example 1 (1) Preparation of bio-based epoxy emulsifier: S101: adding 40 g of bisphenol A epoxy resin into an oil bath, heating to 65° C. and stirring until it is completely melted, then adding 10 g of chitosan, heating the oil bath to 90° C. and reacting for 4 h to obtain a polysaccharide-modified epoxy resin, which is chitosan-modified epoxy resin; S102: Heat all the chitosan-modified epoxy resin obtained in step S101 to 120° C., then add 5 g of cinnamic acid and 0.006 g of tetrabutylammonium bromide catalyst, and react at a constant temperature for 5 hours to obtain a bio-based epoxy emulsifier.
[0068] (2) Preparation of sizing agent (phase inversion method is used in this embodiment): S111: 100 g of bisphenol A epoxy resin is heated to a molten state, and 28 g of a bio-based epoxy emulsifier is added and mixed, and the bisphenol A epoxy resin and the bio-based epoxy emulsifier are stirred and mixed using a high-speed shearing machine; S112: stirring at a speed of 500 rpm for 10 min, after the mixture is evenly stirred, the speed is increased to 2000 rpm, and 360 g of deionized water is slowly added, and the mixture is continued to be stirred; S113: After stirring and mixing evenly, 5 g of polyoxyethylene ether and 6 g of polyether ester amide are added to obtain a sizing agent having the structural formula: .
[0069] (3) Preparation of sizing treated carbon fiber: The commercial carbon fiber was placed in a container filled with acetone and subjected to a desizing treatment at 50° C. for 5 h to obtain a desizing carbon fiber; Then, the carbon fiber was placed in a beaker containing the sizing agent described above and soaked for 5 minutes. The carbon fiber coated with the sizing agent was placed in an oven at 100° C. for 2 minutes to obtain sizing-treated carbon fiber.
[0070] (4) Preparation of carbon fiber / epoxy resin composite materials: Take 6 layers of the above-mentioned sizing-treated carbon fiber cloth, lay them out and put them into the mold, mix the epoxy resin and curing agent diethylenetriamine in a mass ratio of 100:10, remove the bubbles and vacuum inject them into the mold, cure at 105°C for 2h and 125°C for 2h to obtain a carbon fiber / epoxy resin composite material.
[0071] The sizing agent prepared in Example 1 was characterized by infrared chromatogram. The characterization results are shown in Figure 1 In the infrared spectrum, the horizontal axis represents the wave number (wavenumbers), the unit is cm -1 .like Figure 1 As shown, at 1595 cm -1 The absorption peak of NH2 is at 915 cm -1 and 771 cm -1 The characteristic peak at 1710 cm is the absorption peak of the terminal epoxy group. It can be found that the characteristic peaks of the amino group and the epoxy group become smaller, which indicates that bisphenol A epoxy resin reacts with chitosan. -1 The characteristic peak at 1595 cm -1 The weakening of the absorption characteristic peak indicates that the content of amino (-NH2) functional groups decreases. These phenomena indicate that an amide bond (-CONH-) is formed between the amino group (-NH2) of chitosan and the carboxyl group (-COOH) of cinnamic acid.
[0072] Example 2 (1) Preparation of bio-based epoxy emulsifier: S101: adding 50 g of bisphenol F epoxy resin to an oil bath, heating to 60° C. and stirring until it is completely melted, then adding 15 g of carboxymethyl chitosan, heating the oil bath to 80° C. and reacting for 4 h to obtain a polysaccharide-modified epoxy resin, which is carboxymethyl chitosan-modified epoxy resin; S102: Heat all the carboxymethyl chitosan-modified epoxy resin obtained in step S101 to 125° C., then add 10 g of hydroxycinnamic acid and 0.008 g of tetrabutylammonium bromide catalyst, and react at a constant temperature for 8 hours to obtain a bio-based epoxy emulsifier.
[0073] (2) Preparation of sizing agent (self-emulsification method is used in this embodiment): S121: Cool 75 g of bio-based epoxy emulsifier to 60° C., slowly drop 10 g of triethylamine and stir at 500 rpm for 15 min; S122: Increase the speed to 1500 rpm, slowly add 225 g of deionized water, and continue stirring and mixing; S123: After stirring and mixing evenly, 10 g of butyl stearate and 9 g of polyether ester acetamide are added to obtain a sizing agent.
[0074] (3) Preparation of sizing treated carbon fiber: The process of preparing sizing-treated carbon fiber is the same as that in Example 1.
[0075] (4) Preparation of carbon fiber / epoxy resin composite materials: The process of preparing the carbon fiber / epoxy resin composite material is the same as that in Example 1.
[0076] The sizing agent prepared in Example 2 was subjected to thermogravimetric analysis. The thermogravimetric test results are shown in Figure 2 .like Figure 2 As shown in the figure, at 290℃, the sizing agent has a small weight loss of 5%, which is caused by the cleavage of the amide segment in the sizing agent. At 367℃, the weight loss rate of the sizing agent is 87%, which is caused by the thermal decomposition of the sizing agent. It can be seen that the sizing agent has good thermal stability.
[0077] Example 3 S101: 40 g of diphenol propane epoxy resin is added to an oil bath, heated to 80° C. and stirred until it is completely melted, and then 12 g of chitosan oligosaccharide is added, and the oil bath is heated to 95° C. and reacted for 8 hours to obtain a polysaccharide-modified epoxy resin. At this time, the polysaccharide-modified epoxy resin is a chitosan oligosaccharide-modified epoxy resin; S102: Heat all the chitosan-modified epoxy resin obtained in step S101 to 130° C., then add 6 g of butyl cinnamate and 0.006 g of tetrabutylammonium bromide catalyst, and react at a constant temperature for 10 hours to obtain a bio-based epoxy emulsifier.
[0078] (2) Preparation of sizing agent (phase inversion method is used in this embodiment): S111: 100 g of bisphenol A epoxy resin and 28 g of bio-based epoxy emulsifier were stirred and mixed using a high-speed shearing machine; S112: stirring at a rotation speed of 650 rpm for 10 min, after the mixture is evenly stirred, increasing the rotation speed to 2400 rpm, and slowly adding 354 g of deionized water, and continuing to stir and mix; S113: After stirring and mixing evenly, 9 g of higher fatty amine and 6 g of polyethylene oxide are added to obtain a sizing agent.
[0079] (3) Preparation of sizing treated carbon fiber: The process of preparing sizing-treated carbon fiber is the same as that in Example 1.
[0080] (4) Preparation of carbon fiber / epoxy resin composite materials: The other conditions were the same as those in the process of preparing the carbon fiber / epoxy resin composite material in Example 1, except that the curing process was carried out under ultraviolet light irradiation with a light intensity of 25.0 J / cm -2 .
[0081] The surface morphology of the sizing treated carbon fiber prepared in Example 3 was observed using a scanning electron microscope (SEM). The characterization results are as follows: Figure 3 As shown. Figure 3 It can be seen that the surface of the carbon fiber after sizing treatment is evenly coated with the sizing agent, and is smooth and flat.
[0082] Example 4 (1) Preparation of bio-based epoxy emulsifier: S101: 65 g of polyphenol glycidyl ether epoxy resin is added to an oil bath, heated to 100° C. and stirred until it is completely melted, and then 15 g of chitobiose hydrochloride is added, and the oil bath is heated to 110° C. and reacted for 8 hours to obtain a polysaccharide-modified epoxy resin. At this time, the polysaccharide-modified epoxy resin is a chitobiose hydrochloride-modified epoxy resin; S102: Heat all the chitobiose hydrochloride-modified epoxy resins obtained in step S101 to 120° C., then add 10 g of 4-methylcinnamic acid and 0.009 g of tetrabutylammonium bromide catalyst, and react at a constant temperature for 8 hours to obtain a bio-based epoxy emulsifier.
[0083] (2) Preparation of sizing agent (self-emulsification method is used in this embodiment): S121: Cool 90 g of bio-based epoxy emulsifier to 60° C., slowly drop 8 g of triethylamine and stir at 500 rpm for 15 min; S122: Increase the speed to 1500 rpm, slowly add 270 g of deionized water, and continue stirring and mixing; S123: After stirring and mixing evenly, 7 g of higher fatty alcohol and 9 g of propylene oxide copolymer are added to obtain a sizing agent.
[0084] (3) Preparation of sizing treated carbon fiber: The process of preparing sizing-treated carbon fiber is the same as that in Example 1.
[0085] (4) Preparation of carbon fiber / epoxy resin composite materials: The process of preparing the carbon fiber / epoxy resin composite material is the same as that in Example 1.
[0086] The surface morphology of the sizing-treated carbon fiber obtained in Example 4, i.e., the surface morphology of the carbon fiber before recycling, was observed using a scanning electron microscope (SEM). Figure 4 The surface morphology of the carbon fiber / epoxy resin composite material prepared in Example 4 after degradation and recovered was observed using a scanning electron microscope (SEM), that is, the surface morphology characteristics of the recovered carbon fiber, see Figure 5 .like Figure 4 and Figure 5As shown, the surface of the carbon fiber before recycling is evenly wrapped by the sizing agent, while the surface of the carbon fiber after degradation has a large number of grooves, which indicates that the sizing agent is degradable and does not cause any damage to the carbon fiber.
[0087] Among them, before observing the surface morphology of recycled carbon fiber, the composite material needs to be treated as follows:
[0088] 5 g of the carbon fiber / epoxy resin composite material prepared in Example 4 was placed in a glass bottle, 3 mL of acetonitrile and 9 mL of acetic acid solvent were added thereto, and then placed in a 90° C. oil bath for degradation. After the composite material was completely degraded, it was filtered and washed with ethanol to obtain the recovered carbon fiber.
[0089] Meanwhile, degradation analysis was performed on the composite material prepared in Example 4, which proved that the sizing agent provided in this example has the possibility of degradation.
[0090] Comparative Example 1 Preparation of carbon fiber / epoxy resin composites: The carbon fiber cloth coated with a commercial sizing agent was cut into small pieces of 80×80 mm in size, 6 layers of the above small pieces were laid out and put into a mold, epoxy resin and curing agent diethylenetriamine in a mass ratio of 100:10 were mixed and injected into the mold under vacuum after removing bubbles, and cured at 105°C for 2h and 125°C for 2h to obtain a carbon fiber / epoxy resin composite material.
[0091] It should be noted that in the preparation process of commercial sizing agents, one or more of acetone, ethylene glycol monomethyl ether and ethylene glycol butyl ether are usually used, and other organic solvents may also be used, which are only used as examples here.
[0092] Test Case Interlaminar shear strength test Test method: Refer to the provisions of the industry standard JC / T 773-2010 to determine the interlaminar shear strength (ILSS) of fiber reinforced plastics using the short beam method, or refer to the provisions of the national standard GB / T 1450.1-2005 on the test method for interlaminar shear strength of fiber reinforced plastics.
[0093] The test results of the interlaminar shear strength of the carbon fiber / epoxy resin composite materials prepared in Examples 1 to 4 and Comparative Example 1 are shown in Tables 1 and Figure 6 As shown in Table 1 and Figure 6 It can be seen that after the carbon fiber in the present invention is treated with sizing, the interfacial adhesion with the matrix is significantly enhanced, and the mechanical properties of the composite material are significantly improved.
[0094] Table 1: Interlaminar shear strength of carbon fiber / epoxy resin composites prepared in Examples 1 to 4 and Comparative Example 1 Carbon fiber / epoxy resin composite material Interlaminar shear strength / MPa Example 1 71.14 Example 2 76.36 Example 3 72.48 Example 4 73.57 Comparative Example 1 62.54 .
[0095] Particle size testing Test method: The average particle size of the sizing agents prepared in Examples 1 to 4 and Comparative Example 1 was obtained by testing with a Zetasizer NanoZS90 dynamic laser scattering instrument produced by Malvern Instruments.
[0096] Particle size has an important influence on the stability, distribution uniformity and interaction of sizing agent with carbon fiber. As shown in Table 2 below, Example 2 and Example 4 show a smaller particle size, which helps the sizing agent to be more evenly distributed on the surface of carbon fiber. In combination with Table 1 and Table 2, it can be seen that different particle sizes have slightly different interfacial properties of carbon fiber composite materials, and smaller particle sizes have a significant effect on improving the mechanical properties of carbon fiber composite materials. Specifically, the sizing agent with a smaller particle size can make its coating on the surface of carbon fiber more uniform, thereby making the surface of the carbon fiber after coating smoother, and the interface thickness is thinner, which is conducive to the full combination and reaction of carbon fiber and epoxy resin. As can be seen from the foregoing, the sizing agent of Example 2 and Example 4 is prepared by self-emulsification method, and the sizing agent of Example 1 and Example 3 is prepared by phase inversion method. Therefore, the interfacial performance of the carbon fiber / epoxy resin composite material prepared by self-emulsification method is better than that of the composite material prepared by phase inversion method. Although the interfacial performance of the composite material obtained by the sizing agent prepared by phase inversion method is low, the method is simple to operate, low cost and high degree of industrialization. The present invention does not limit the preparation method of the sizing agent, and a self-emulsification method or a phase inversion method may be used according to actual conditions.
[0097] pH Test Test method: The pH value of the sizing agent was obtained by using a DELTA 320 pH meter from Mettler-Toledo, USA.
[0098] The change of pH value will affect the chemical stability of the sizing agent and the interaction with the fiber, and then affect the dyeing performance and feel of the fiber. As shown in Table 2 below, the pH values of Comparative Example 1 and all the examples are mostly close to neutral, which may contribute to the stability and storage performance of the product.
[0099] Viscosity test Test method: Brookfield DV-II Pro rotational viscometer is used to test the viscosity of the sizing agent.
[0100] The viscosity directly affects the sizing rate, the ratio of penetration to coating, and the thickness of the sizing film. As shown in Table 2, the viscosity of the sizing agents in Examples 1 to 4 is significantly lower than that of the commercial sizing agent in Comparative Example 1. Therefore, the sizing agent prepared with the bio-based epoxy emulsifier helps to improve its sizing performance, including the sizing rate, the ratio of penetration to coating, and the thickness of the sizing film.
[0101] Stiffness test Test method: According to the stiffness determination performance in Part 4 of GB / T 7690.4-2013 Test method for reinforcing material yarn, the stiffness of the carbon fiber is characterized.
[0102] Stiffness testing helps to understand the effect of sizing agents on the shape and structure of textiles. Higher stiffness helps textiles maintain their shape, which may improve product performance. Figure 2 As shown, the stiffness of Examples 1 to 4 is greater than that of Comparative Example 1, so the sizing-treated carbon fiber provided by the present invention can better maintain its shape and has better performance than commercial carbon fiber. Among them, the stiffness of Example 2 reaches 98cm, while the stiffness of Comparative Example 1 is 92cm, which shows that the carbon fiber prepared in Example 2 has the best effect.
[0103] Hair volume test Test method: The fuzz content of carbon fiber is obtained according to GB-T 41956-2022 Determination of the fuzz content of carbon fiber tow.
[0104] By testing the amount of fuzz, the effect of the sizing agent on reducing carbon fiber fuzz can be evaluated. As shown in Table 2 below, the amount of fuzz of the carbon fibers prepared in Examples 1 to 4 is lower than the amount of fuzz of the carbon fibers in Comparative Example 1, which indicates that the sizing agent prepared by the bio-based epoxy emulsifier in the present invention is effective in reducing carbon fiber fuzz.
[0105] Comprehensive stiffness and fuzz test results show that the performance of carbon fiber / epoxy resin composites can be significantly improved by sizing carbon fiber with a sizing agent made from a bio-based epoxy emulsifier.
[0106] Table 2: Particle size, pH value and viscosity of sizing agent and stiffness and amount of fuzz of carbon fiber in Examples 1 to 4 and Comparative Example 1 Comparative Example 1 Example 1 Example 2 Example 3 Example 4 Particle size / nm 308 278 156 285 178 pH 6.89 7.68 7.06 7.45 7.32 Viscosity / cp 37.8 35.4 28.5 34.2 29.5 Stiffness / cm 92 95 98 93 95 Hair amount / mg 2.45 2.32 1.98 2.13 2.34 .
[0107] In summary, the sizing agents, carbon fibers and composite materials made therefrom of Examples 1-4 are superior to commercial sizing agents and their corresponding products in terms of performance, stability and cost-effectiveness.
Claims
1. A bio-based epoxy emulsifier, characterized in that: The raw materials of the bio-based epoxy emulsifier include the following components: polysaccharide, epoxy resin, phenolic acid and catalyst; The preparation method of the bio-based epoxy emulsifier comprises the following steps: S101: heating the epoxy resin to 50-100° C. until it is completely melted, adding polysaccharide, and reacting at 80-110° C. for 4-15 hours to obtain a polysaccharide-modified epoxy resin; S102: Heat the polysaccharide-modified epoxy resin to 120-200° C., then add phenolic acid and a catalyst, and react for 5-18 hours to obtain a bio-based epoxy emulsifier.
2. The bio-based epoxy emulsifier according to claim 1, characterized in that In step S101, the mass ratio of polysaccharide to epoxy resin is 1:(3-4.5).
3. The bio-based epoxy emulsifier according to claim 1, characterized in that In step S102, the mass ratio of the polysaccharide-modified epoxy resin to the phenolic acid is 1:(0.1-1), and the mass of the catalyst accounts for 0.001%-0.008% of the total mass of the raw materials.
4. The bio-based epoxy emulsifier according to claim 1, characterized in that Bio-based epoxy emulsifiers have one or more of the following characteristics: The polysaccharide is selected from one or more of chitosan, chitosan derivatives and chitobiose hydrochloride, and the chitosan derivative is selected from one or more of carboxymethyl chitosan and chitosan oligosaccharide; The epoxy resin is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, diphenol propane type epoxy resin and polyphenol type glycidyl ether epoxy resin; The phenolic acid is selected from one or more of cinnamic acid and cinnamic acid derivatives, and the cinnamic acid derivative is selected from one or more of hydroxycinnamic acid, butyl cinnamate and 4-methylcinnamic acid; The catalyst includes tetrabutylammonium bromide.
5. A sizing agent, characterized in that It comprises a bisphenol A epoxy resin in a mass ratio of 1: (0.25-0.37): (3.34-4): (0.007-0.13): (0.007-0.13), a bio-based epoxy emulsifier as claimed in claim 1, water, a lubricant and an antistatic agent.
6. The sizing agent according to claim 5, characterized in that The structural formula of the sizing agent is: 。 7. The sizing agent according to claim 5, characterized in that The preparation method of the sizing agent is: S111: heating the bisphenol A epoxy resin to a molten state, adding the bio-based epoxy emulsifier to the mixture, and stirring and mixing the bisphenol A epoxy resin and the bio-based epoxy emulsifier with a high-speed shearing machine; S112: After the mixture is stirred and mixed evenly, the rotation speed is increased and water is slowly added to continue stirring and mixing; S113: After stirring and mixing evenly, a lubricant and an antistatic agent are added to obtain a sizing agent.
8. A sizing agent comprising the bio-based epoxy emulsifier according to claim 1, amines, water, a lubricant and an antistatic agent in a mass ratio of 1: (0.01-0.15): (2.6-3): (0.007-0.13): (0.007-0.13).
9. The sizing agent according to claim 8, characterized in that The preparation method of the sizing agent is: S121: Cool the bio-based epoxy emulsifier to 50-70°C, then add the amine and stir to mix; S122: Increase the stirring speed to 1000-2000 rpm, slowly add water, and continue stirring and mixing; S123: After stirring and mixing evenly, a lubricant and an antistatic agent are added to obtain a sizing agent.
10. A sizing treated carbon fiber, characterized in that: The sizing-treated carbon fiber is obtained by sizing carbon fiber using the sizing agent according to any one of claims 5 to 9.
11. A carbon fiber / epoxy resin composite material, characterized in that: The carbon fiber / epoxy resin composite material is prepared by curing the sizing-treated carbon fiber as claimed in claim 10, epoxy resin and curing agent in a mass ratio of 1:(100-200):(10-20).
Citation Information
Patent Citations
Temperature tolerance type carbon fibre emulsion sizing agent and its preparation process and application
CN100500984C
Macro-molecule emulsifier self-emulsified epoxy resin sizing agent for carbon fiber
CN104452303A
Phenolic acid grafted chitooligosaccharide, preparation method and application thereof to modified waterborne polyurethane
CN108676108A
Bisphenol acid-based epoxy resin emulsifier, and water-based emulsion and preparation method thereof
CN111454466A
Bio-based epoxy resin emulsifier as well as water-based emulsion and preparation method thereof
CN111607105A
Cited By
Polysaccharide derivative and application thereof in epoxy emulsifier
CN122587094A